Alteration of glycosphingolipid metabolism by ozone is associated with exacerbation of allergic asthma characteristics in mice. (4th November 2022) - Stevens, Nathanial C; Brown, Veneese J; Domanico, Morgan C; Edwards, Patricia C; Van Winkle, Laura S; Fiehn, Oliver
Abstract: Asthma is a common chronic respiratory disease exacerbated by multiple environmental factors. Acute ozone exposure has previously been implicated in airway inflammation, airway hyperreactivity, and other characteristics of asthma, which may be attributable to altered sphingolipid metabolism. This study tested the hypothesis that acute ozone exposure alters sphingolipid metabolism within the lung, which contributes to exacerbations in characteristics of asthma in allergen-sensitized mice. Adult male and female BALB/c mice were sensitized intranasally to house dust mite (HDM) allergen on days 1, 3, and 5 and challenged on days 12–14. Mice were exposed to ozone following each HDM challenge for 6 h/day. Bronchoalveolar lavage, lung lobes, and microdissected lung airways were collected for metabolomics analysis ( N = 8/sex/group). Another subset of mice underwent methacholine challenge using a forced oscillation technique to measure airway resistance ( N = 6/sex/group). Combined HDM and ozone exposure in male mice synergistically increased airway hyperreactivity that was not observed in females and was accompanied by increased airway inflammation and eosinophilia relative to control mice. Importantly, glycosphingolipids were significantly increased following combined HDM and ozone exposure relative to controls in both male and female airways, which was also associated with both airway resistance and eosinophilia. However, 15 glycosphingolipid species were increased in females compared with only 6 in males, which was concomitant with significant associations between glycosphingolipids and airway resistance that ranged from R 2 = 0.33–0.51 for females and R 2 = 0.20–0.34 in male mice. These observed sex differences demonstrate that glycosphingolipids potentially serve to mitigate exacerbations in characteristics of allergic asthma.